- 23+(3x8)
- 19+(30-8)
- 2(3+9)
- 3(14+19)

Learning resources for Find the Equivalent Algebraic Expressions such as questions and answers, worksheets, quizzes, online tests, calculator, examples, step by step answers, practice problems, challenges to explore, learn, practice, solve homework problems, solve assignments and assess the learning objectives.

Name
Grade
School

Date
Questions20
Score

1

9(1+10) =

- 23+(3x8)
- 19+(30-8)
- 2(3+9)
- 3(14+19)

2

2(5+12) =

- 2x11
- 2x17
- 2x47
- 32+(3x13)

3

3x19 =

- 2(14-4)
- 3(8+11)
- 5(6+13)
- 26+(43-10)

4

16+(3x7) =

- 18+(23-4)
- 2(2+12)
- 4(5+6)
- 26+(41-6)

5

3x7 =

- 5x7
- 3(38-6)
- 3(3+4)
- 4(13-8)

6

5x11 =

- 9(0+9)
- 5(1+10)
- 2(19+24)
- 8(2+6)

7

2(5+6) =

- 2(2+4)
- 26+(3x9)
- 2x11
- 5+(2x7)

8

35+(2x19) =

- 17+(30-4)
- 4(7+15)
- 2(21+24)
- 35+(46-8)

9

3x9 =

- 2(0+10)
- 3(0+9)
- 4(4+7)
- 7(12-3)

10

2(18+23) =

- 3(13+16)
- 2(18+26)
- 16+(5x5)
- 2x41

11

46+(3x17) =

- 3x7
- 3(12+20)
- 46+(58-7)
- 37+(3x14)

12

2(6+16) =

- 7+(2x5)
- 2(36-4)
- 4(4+7)
- 3(1+4)

13

4+(14-5) =

- 4(27-6)
- 16+(5x5)
- 4+(3x3)
- 2(6+8)

14

2(4+5) =

- 3(1+5)
- 2(-2+7)
- 6(4+7)
- 38+(5x9)

15

2(3+7) =

- 2(16-4)
- 5(3+9)
- 4(8-3)
- 2(10+17)

16

3x5 =

- 19+(27-3)
- 5x19
- 3(1+4)
- 27+(39-5)

17

2(35-7) =

- 2(24-10)
- 4(18-4)
- 32+(41-2)
- 2(41-9)

18

17+(35-9) =

- 2(9+16)
- 17+(2x13)
- 4(12+13)
- 7(5+8)

19

2(8+11) =

- 2(3+6)
- 4(2+3)
- 5(8+9)
- 2x19

20

3x11 =

- 5(1+5)
- 2(15-5)
- 2(7+14)
- 3(2+9)

Answers Key

Show All Workout

1

9(1+10) = 3(14+19)

Solution

9(1+10) = 9 x 11 = 99

3(14+19) = 3 x 33 = 99

Hence 9(1+10) = 3(14+19)

3(14+19) = 3 x 33 = 99

Hence 9(1+10) = 3(14+19)

2

2(5+12) = 2x17

Solution

2(5+12) = 2 x 17 = 34

2 x 17 = 34

Hence 2(5+12) = 2x17

2 x 17 = 34

Hence 2(5+12) = 2x17

3

3x19 = 3(8+11)

Solution

3 x 19 = 57

3(8+11) = 3 x 19 = 57

Hence 3x19 = 3(8+11)

3(8+11) = 3 x 19 = 57

Hence 3x19 = 3(8+11)

4

16+(3x7) = 18+(23-4)

Solution

16+(3x7) = 16 + 21 = 37

18+(23-4) = 18 + 19 = 37

Hence 16+(3x7) = 18+(23-4)

18+(23-4) = 18 + 19 = 37

Hence 16+(3x7) = 18+(23-4)

5

3x7 = 3(3+4)

Solution

3 x 7 = 21

3(3+4) = 3 x 7 = 21

Hence 3x7 = 3(3+4)

3(3+4) = 3 x 7 = 21

Hence 3x7 = 3(3+4)

6

5x11 = 5(1+10)

Solution

5 x 11 = 55

5(1+10) = 5 x 11 = 55

Hence 5x11 = 5(1+10)

5(1+10) = 5 x 11 = 55

Hence 5x11 = 5(1+10)

7

2(5+6) = 2x11

Solution

2(5+6) = 2 x 11 = 22

2 x 11 = 22

Hence 2(5+6) = 2x11

2 x 11 = 22

Hence 2(5+6) = 2x11

8

35+(2x19) = 35+(46-8)

Solution

35+(2x19) = 35 + 38 = 73

35+(46-8) = 35 + 38 = 73

Hence 35+(2x19) = 35+(46-8)

35+(46-8) = 35 + 38 = 73

Hence 35+(2x19) = 35+(46-8)

9

3x9 = 3(0+9)

Solution

3 x 9 = 27

3(0+9) = 3 x 9 = 27

Hence 3x9 = 3(0+9)

3(0+9) = 3 x 9 = 27

Hence 3x9 = 3(0+9)

10

2(18+23) = 2x41

Solution

2(18+23) = 2 x 41 = 82

2 x 41 = 82

Hence 2(18+23) = 2x41

2 x 41 = 82

Hence 2(18+23) = 2x41

11

46+(3x17) = 46+(58-7)

Solution

46+(3x17) = 46 + 51 = 97

46+(58-7) = 46 + 51 = 97

Hence 46+(3x17) = 46+(58-7)

46+(58-7) = 46 + 51 = 97

Hence 46+(3x17) = 46+(58-7)

12

2(6+16) = 4(4+7)

Solution

2(6+16) = 2 x 22 = 44

4(4+7) = 4 x 11 = 44

Hence 2(6+16) = 4(4+7)

4(4+7) = 4 x 11 = 44

Hence 2(6+16) = 4(4+7)

13

4+(14-5) = 4+(3x3)

Solution

4+(14-5) = 4 + 9 = 13

4+(3x3) = 4 + 9 = 13

Hence 4+(14-5) = 4+(3x3)

4+(3x3) = 4 + 9 = 13

Hence 4+(14-5) = 4+(3x3)

14

2(4+5) = 3(1+5)

Solution

2(4+5) = 2 x 9 = 18

3(1+5) = 3 x 6 = 18

Hence 2(4+5) = 3(1+5)

3(1+5) = 3 x 6 = 18

Hence 2(4+5) = 3(1+5)

15

2(3+7) = 4(8-3)

Solution

2(3+7) = 2 x 10 = 20

4(8-3) = 4 x 5 = 20

Hence 2(3+7) = 4(8-3)

4(8-3) = 4 x 5 = 20

Hence 2(3+7) = 4(8-3)

16

3x5 = 3(1+4)

Solution

3 x 5 = 15

3(1+4) = 3 x 5 = 15

Hence 3x5 = 3(1+4)

3(1+4) = 3 x 5 = 15

Hence 3x5 = 3(1+4)

17

2(35-7) = 4(18-4)

Solution

2(35-7) = 2 x 28 = 56

4(18-4) = 4 x 14 = 56

Hence 2(35-7) = 4(18-4)

4(18-4) = 4 x 14 = 56

Hence 2(35-7) = 4(18-4)

18

17+(35-9) = 17+(2x13)

Solution

17+(35-9) = 17 + 26 = 43

17+(2x13) = 17 + 26 = 43

Hence 17+(35-9) = 17+(2x13)

17+(2x13) = 17 + 26 = 43

Hence 17+(35-9) = 17+(2x13)

19

2(8+11) = 2x19

Solution

2(8+11) = 2 x 19 = 38

2 x 19 = 38

Hence 2(8+11) = 2x19

2 x 19 = 38

Hence 2(8+11) = 2x19

20

3x11 = 3(2+9)

Solution

3 x 11 = 33

3(2+9) = 3 x 11 = 33

Hence 3x11 = 3(2+9)

3(2+9) = 3 x 11 = 33

Hence 3x11 = 3(2+9)

Math Challenge

Start my Challenge

Equivalent algebraic equation for 7(21-7) is

Equivalent algebraic equation for 7(14-5) is

Equivalent algebraic equation for 3(9+19) is

Equivalent algebraic equation for 3x19 is

Equivalent algebraic equation for 2(4+5) is

Equivalent algebraic equation for 40+(52-3) is

Equivalent algebraic equation for 2(10+13) is

Equivalent algebraic equation for 3(-2+7) is

Equivalent algebraic equation for 2(3+7) is

Equivalent algebraic equation for 7(4+7) is

Copyright Reserved 2021©

MATH LEARNING RESOURCES AND TOOLS FOR PERSONALIZED LEARNING